Ecotourism in Puglia Region, Italy – A Competitive Advantage in the Current Context - Daniel Avram; Alina-Cerasela Avram (Ovidius University Annals: Economic Sciences Series, 2020)
Italy is one of the most attractive destinations in the world and represents a reference point for international tourism. The impressive number of tourists flows concentrated, especially in the northern part of the country has caused many issues among the local population. In this context, rethinking tourism activity and make it more sustainable becomes essential. A first solution can come from the Puglia region, which is one of the main ecotourism destinations of the country. This article describes the image of Puglia in the online environment and investigates whether tourists also perceive this region as an ecotourism one. Based on the experience of the stakeholders in the region regarding ecotourism activity, and taking into account the actual context caused by the COVID-19 health crisis, Puglia can take momentum and consolidate its brand on the international market.